INDENTIFIKASI SENYAWA EKSTRAK UMBI GARUT DAN TEPUNG IKAN LELE DUMBO MELALUI UJI FITOKIMIA SEBAGAI IMUNOSTIMULAN PADA TIKUS PUTIH YANG DI INDUKSI VAKSIN HEPATITIS B - Zulkifli, Zulkifli; Jamil, Kurnian Fitri; Darmawi, Darmawi; Usman, Said (Jurnal Farmanesia, 2022)
The variety of biodiversity that grows in Indonesia makes this country the second megacenter in the world after Brazil. More than 30,000 plant species grow and 2,500 of them are medicinal plants one of them is arrowroot (Maranta arundinacea) as well as natural sources of animal wealth such as Dumbo catfish (Powder Clarias gariepinus) which is a source of protein that is needed by the body. Several researchers have also investigated the active compounds contained in the two ingredients, but differences in the environment and the maintenance process significantly affect the chemical content. This research focused on the initial phytochemical test and chemical composition of Maranta arundinacea extract and Clarias gariepinus powder extracted with 40% ethanol by maceration and hydrolysis techniques